2012
DOI: 10.1089/vbz.2011.0753
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Control of Human Granulocytic Anaplasmosis: A Systematic Review

Abstract: Granulocytic anaplasmosis caused by Anaplasma phagocytophilum is an emerging tick-borne zoonosis worldwide. The obligate intracellular pathogen is transmitted by Ixodes ticks and infects neutrophils in humans and animals, resulting in clinical symptoms ranging from asymptomatic seroconversion to mild, severe, or fatal disease. Since the initial description of human granulocytic anaplasmosis (HGA) in the United States in 1990, HGA has been increasingly recognized in America, Europe, and Asia. This review descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 74 publications
1
52
0
1
Order By: Relevance
“…In Europe, no death has been reported to be associated with HGA, suggesting that in European regions the main disease produced by A. phagocytophilum is TBF in sheep while in the United States HGA predominates. Cross-infection experiments indicate that A. phagocytophilum isolates of distinct host origin are not uniformly infectious for heterologous hosts (Jin et al, 2012). Recently, multilocus sequence typing of almost 400 A. phagocytophilum strains from humans and animals has shown that strains from humans, dogs, horses, wild boars and hedgehogs from Europe belong to the same clonal complex whereas cattle, sheep, roe deer, vole and shrew strains are distantly related suggesting that they are unlikely to be infectious for humans (Huhn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, no death has been reported to be associated with HGA, suggesting that in European regions the main disease produced by A. phagocytophilum is TBF in sheep while in the United States HGA predominates. Cross-infection experiments indicate that A. phagocytophilum isolates of distinct host origin are not uniformly infectious for heterologous hosts (Jin et al, 2012). Recently, multilocus sequence typing of almost 400 A. phagocytophilum strains from humans and animals has shown that strains from humans, dogs, horses, wild boars and hedgehogs from Europe belong to the same clonal complex whereas cattle, sheep, roe deer, vole and shrew strains are distantly related suggesting that they are unlikely to be infectious for humans (Huhn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Anaplasma phagocytophilum is thought to be maintained naturally in small mammal-tick cycles, with Ixodes ticks as vectors (Bown et al, 2003;Dumler et al, 2001). A wide range of mammals serve as reservoir hosts in the natural life cycle of Anaplasma phagocytophilum (Jin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Anaplasmosis is the second most common tickborne disease in North America, and its reported incidence has doubled over the last decade (6). A. phagocytophilum encompasses a heterogeneous group of strains, some of which infect rodents, deer, and horses, but the primary reservoir of human-infective strains is thought to be the white-footed mouse (18). A. phagocytophilum belongs to the Rickettsiales order, which includes emerging arthropod-transmitted pathogens such as Ehrlichia spp.…”
mentioning
confidence: 99%